2016
DOI: 10.1039/c5sc04197j
|View full text |Cite
|
Sign up to set email alerts
|

A new Pseudomonas quinolone signal (PQS) binding partner: MexG

Abstract: Pseudomonas Quinolone Signal (PQS) probes capture a new binding partner for this signal molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…We calculated a K D of pyocyanin to MexG to be about 0.6 μM (Figure 5C). This suggests that the binding is quite strong, with the K D is similar to what was previously reported for MexG and PQS 23 .…”
Section: Resultssupporting
confidence: 88%
“…We calculated a K D of pyocyanin to MexG to be about 0.6 μM (Figure 5C). This suggests that the binding is quite strong, with the K D is similar to what was previously reported for MexG and PQS 23 .…”
Section: Resultssupporting
confidence: 88%
“…To support this hypothesis, PQS is associated with the MexGHI-OpmD efflux pump, which controls antibiotic susceptibility through the production of PQS and N-acyl-L-homoserine lactone QS signal molecules and is also regulated by VqsR (44,67). A recent study demonstrates that MexG is capable of binding PQS (68). The studies by Wu et al demonstrated that the pro-oxidant paraquat promoted antibiotic tolerance, underscoring the importance of oxidative stress in antibiotic tolerance (69).…”
Section: Discussionmentioning
confidence: 99%
“…PQS and HQNO contain primary alkyl groups that could be coupled to an Affi-gel 10 (Bio-Rad, Hercules, CA, USA) matrix68. The compound–matrix coupling was performed by incubation of 1.5 ml Affi-gel media with 0.3 mg of each compound and incubated at 4 °C for 2 h following the Bio-Rad's manual.…”
Section: Methodsmentioning
confidence: 99%